Draft Ninth Five Year Plan 1997-2002 Volume - I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 1997)
Rajasthan evokes colourful image of a land of chivalrous rulers, brave and beautiful women, bedecked camels dotting the desert landscape, rich folklore and friendly people. In the last fifty years, it has emerged as the major tourist destination in India, for both the domestic and foreign tourists. Jaipur, the Pink City; Udaipur, the City of Lakes; Jaisalmer, the Dream City of ‘Sonar Kila’ (the Golden Fort), Bharatpur with its Keoladevi Bird National Park-are all a part of the legend of the State which has been the romance of the birds and the poets for centuries.
Government of Rajasthan, Planning Department
Government of Rajasthan